Evaluating counselling skills of community health workers for pregnant adolescents in Limpopo province - Rakgadi G. Malapela; Sheillah H. Mboweni; Patrone R. Risenga (South African Journal of Psychiatry, 2024)
Background: Adolescent pregnancy carries significant global ramifications. Community health workers (CHWs) play a role in empowering adolescents through counselling skills, thereby promoting informed decision-making for better outcomes.